Socioeconomic and academic consequences of COVID-19 pandemic on medical students from the University of Rwanda. - Olga Nadege Uwera Ndamukunda; Marie Therese Mutuyimana; Fabiola Umubano; Eugene Tuyishime (PLoS ONE)
Introduction Little is known about the consequences of the COVID-19 pandemic on the life of university students in Sub Saharan Africa (SSA). The objective of this study was to evaluate the socioeconomic and academic consequences of the COVID-19 pandemic on medical students studying at the University of Rwanda. Methods This was a cross-sectional study. An online survey using google form was sent to medical students in clinical training (year 3 till year 5) using convenience sampling followed by snowball sampling method. We collected data on participants' demographics, general knowledge on the COVID-19 pandemic and perception on mitigation measures, and socio-economic and academic consequences of the COVID-19 pandemic. Descriptive statistics were used in excel 2015 software to calculate participants' responses and categorical data were presented using frequencies and percentages. Results A total 187 participants completed the survey. Most participants described disruption in routine activities (72.7%), reduced travelling (69%), church closing (64.2%), and loss of freedom (57.2%) as examples of negative social consequences. While financial uncertainty (64.7%), decrease in income (49.7%), and increase in poverty rate (42.2%) were the main economic consequences. Issues with academic progress (95.7%), limited social life (56.1%), and repeating the year (42.8%) were examples of negative academic consequences. Conclusion The results of this study suggest that the COVID-19 had a negative social, economic, and academic consequences on medical students at the University of Rwanda. These finding may guide the design of interventions to mitigate the consequences of COVID-19 and to protect medical students against future pandemics and crises.